The cry for professional intimacy: a UK study of changes in the working lives of expert practitioners in health and education during the early 21st century - Birkbeck, Fiona (2018)
This is a qualitative study investigating the impact of factors affecting the working lives of practitioners in Health and Education during the period 2006-2016. It was conducted in the context of the increasing evidence of low recruitment, low retention rates and a high incidence of stress amongst expert practitioners in these two public institutions. What emerges from the data is a cross-sector phenomenon identified here as a ‘cry for professional intimacy’, formed as these practitioners give voice to a strong desire to be allowed to refocus on the relational aspects of their work.